GE_GERICHTE P/22003/2024 vom 23. Mai 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;FAUX INTELLECTUEL DANS LES TITRES;TESTAMENT PUBLIC;NOTAIRE;NÉGLIGENCE;PRESCRIPTION | CPP.310; CPP.317; CPP.317.ch2